Tundra Underlain By Thawing Permafrost Persistently Emits Carbon to the Atmosphere Over 15 Years of Measurements. Issue 6 (8th June 2021) - Schuur, Edward A.G.; Bracho, Rosvel; Celis, Gerardo; Belshe, E. Fay; Ebert, Chris; Ledman, Justin; Mauritz, Marguerite; Pegoraro, Elaine F.; Plaza, César; Rodenhizer, Heidi; Romanovsky, Vladimir; Schädel, Christina; et al.
Abstract: Warming of the Arctic can stimulate microbial decomposition and release of permafrost soil carbon (C) as greenhouse gases, and thus has the potential to influence climate change. At the same time, plant growth can be stimulated and offset C release. This study presents a 15‐year time series comprising chamber and eddy covariance measurements of net ecosystem C exchange in a tundra ecosystem in Alaska where permafrost has been degrading due to regional warming. The site was a carbon dioxide source to the atmosphere with a cumulative total loss of 781.6 g C m −2 over the study period. Both gross primary productivity (GPP) and ecosystem respiration ( R eco ) were already likely higher than historical levels such that increases in R eco losses overwhelmed GPP gains in most years. This shift to a net C source to the atmosphere likely started in the early 1990s when permafrost was observed to warm and thaw at the site. Shifts in the plant community occur more slowly and are likely to constrain future GPP increases as compared to more rapid shifts in the microbial community that contribute to increased R eco . Observed rates suggest that cumulative net soil C loss of 4.18–10.00 kg C m −2 —8%–20% of the current active layer soil C pool—could occur from 2020 to the end of the century. This amount of permafrost C loss to the atmosphere represents a significant accelerating feedback to climate change if it were to occur at a similar magnitude across the permafrost region. Plain Language Summary: The Arctic is warming at twice the global average. Shifting environmental conditions including the degradation of permafrost affect the storage of carbon in plants and soils of tundra ecosystems. Carbon uptake by plant growth and carbon release by microbial respiration of soil organic matter both appear to have increased prior to and over 15 years of measurements in a tundra ecosystem in Alaska where permafrost has been degrading. But, carbon release to the atmosphere overwhelmed uptake on average, which leads to net release of carbon to the atmosphere and accelerates climate change. Key Points: Fifteen years of measurements reveal tundra to be a persistent annual net source of carbon to the atmosphere where permafrost is degrading Plant and microbial activity increased from historical levels such that respiration losses in most years overwhelmed productivity gains The longer successional dynamics of plants suggests that respiration may outpace productivity for decades as an accelerating feedback to climate change